SPE Gas Technology Symposium 2002
DOI: 10.2118/75720-ms
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Water Coning in Gas Wells

Abstract: Theoretical study, reported in this paper, qualifies unique mechanisms of water coning in gas wells. Water coning in gas wells has been understood as a phenomenon similar to that in the oil wells. It is shown, however that both the water inflow mechanism and its impact on well's productivity are substantially different. It is shown, for example, that, after water breakthrough, the oil-water interface at the well's completion would continue to cone, while the gas-water interface reverses at the top of the cone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This could result in a change in water permeability of the rock and could lead to a so-called water coning effect, wherein a water channel could over time open up into a water pocket. The well may then be irreversibly damaged and will never be able to reach its optimal productivity again (Armenta and Wojtanowicz 2002;Hatzignatiou and Mohamed 1994;Okon et al 2017). The precipitated inhibitors can cause clogging of pores or formation damage Przybylinski 1989), thus, reducing the permeability of the rock formation which can cause reduced fluid flow.…”
Section: Models For Squeeze Treatmentsmentioning
confidence: 99%
“…This could result in a change in water permeability of the rock and could lead to a so-called water coning effect, wherein a water channel could over time open up into a water pocket. The well may then be irreversibly damaged and will never be able to reach its optimal productivity again (Armenta and Wojtanowicz 2002;Hatzignatiou and Mohamed 1994;Okon et al 2017). The precipitated inhibitors can cause clogging of pores or formation damage Przybylinski 1989), thus, reducing the permeability of the rock formation which can cause reduced fluid flow.…”
Section: Models For Squeeze Treatmentsmentioning
confidence: 99%
“…The root cause of water production in gas reservoirs is the water coning of gas wells. In 2002, Armenta and Wojtanowicz 2 studied on mechanisms of water coning in gas wells based on the factors of non-Darcy flow, perforation density, and the ratio of vertical-to-horizontal permeability, they found that the early water breakthrough and the large increase in water production may be the result of the combined effects of increased vertical permeability, a lower density of perforation, and high-velocity gas flow around the wells. In 2015, Feng et al 3 proposed that water influx activity is related to the volume ratio of movable water to gas in the connected area, the contact area between gas and water, and the permeability difference between gas and water zone.…”
Section: Introductionmentioning
confidence: 99%
“…In general, water production is not a favorable occurrence. Reducing well productivity, water separation and handling, corrosion and environmental issues are the major challenges associated with water coning phenomena (Armenta andWojtanowicz, 2002, Bahadori andNouri, 2012;Mauriya et al, 2014;Carpenter, 2015;Moortgat and Firoozabadi, 2016;Kamari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%